Qualification of the airborne FTIR spectrometer MIPAS-STR and study on denitrification and chlorine deactivation in Arctic winter 2009/10 - Woiwode, Wolfgang (KIT Scientific Publishing, 2013)
This work describes the qualification of the airborne Fourier-Transform infrared spectrometer Michelson Interferometer for Passive Atmospheric Sounding-STRatospheric aircraft (MIPAS-STR) and studies on ozone-relevant processes in the Arctic winter stratosphere. Using MIPAS-STR measurements, correlative in-situ measurements and simulations of the Chemical Lagrangian Model of the Stratosphere (CLaMS), the processes denitrification and chlorine deactivation are investigated.